2011
DOI: 10.1002/eji.201141439
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of autoreactive B cells in humanized SCID mouse model of SLE

Abstract: Although the exact etiology of systemic lupus erythematosus (SLE) remains elusive, B-cell hyperactivity and production of autoantibodies directed to components of the cell nucleus are a well-established pathogenetic mechanism of the disease. Therefore, the targeted inhibition of DNA-specific B cells is a logical therapeutic approach. The complement receptor type 1 (CR1, CD35) has been shown to suppress human B-cell activation and proliferation after co-cross-linking with the BCR, and may serve as a mediator fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 50 publications
2
31
0
Order By: Relevance
“…This suggests that the aberrant expression of CR1 contributes to initiation of autoimmune diseases rather than altering peripheral activation of the cells [10]. The ability of human CR1 to reduce autoimmunity has also been proven in humanized SCID mice transferred with PBMCs of lupus patients where cross-linking of the BCR and CR1 restored B cell tolerance and lowered the number of IgG anti-DNA producing plasma cells [17]. …”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the aberrant expression of CR1 contributes to initiation of autoimmune diseases rather than altering peripheral activation of the cells [10]. The ability of human CR1 to reduce autoimmunity has also been proven in humanized SCID mice transferred with PBMCs of lupus patients where cross-linking of the BCR and CR1 restored B cell tolerance and lowered the number of IgG anti-DNA producing plasma cells [17]. …”
Section: Introductionmentioning
confidence: 99%
“…The first chimera was constructed by coupling copies of the dsDNA‐mimicking peptide to a mouse anti‐human CD35 monoclonal antibody. Its administration to humanized SCID mice reconstituted with PBMCs from SLE patients resulted in the suppression of IgG anti‐DNA antibody‐producing plasma cell, proteinuria and glomerular deposition of human IgG immune complexes . The second chimeric molecule contained copies of the Der p 1‐derived peptide sequence (p52–71) from Dermatophagoides pteronyssinus coupled to the same anti‐human CD35 antibody.…”
Section: Discussionmentioning
confidence: 99%
“…that the human CD35 can provide a strong inhibitory signal to human B lymphocytes . We have previously shown that the binding of specific epitopes to the B cell receptors and the cross‐linking with CD35 on the surface of autoreactive cells may have a strong negative effect on them . The goal of our research is to selectively suppress anti‐GAD65 IgG antibody‐producing B lymphocytes from T1DM patients by chimeric protein molecules that contain a monoclonal antibody, specific to CD35 conjugated to peptide epitopes from GAD65.…”
Section: Introductionmentioning
confidence: 99%
“…These results give evidence that human CR1 exerts an opposite effect to CR2, thus provides an additional level of regulation of humoral immunity (Figure ). The therapeutic potential of CR1 inhibition was proven in a humanized SCID model, where selective co‐cross‐linking native DNA‐specific BCR with the inhibitory CR1 suppressed B‐cell proliferation and autoantibody production . The inhibitory effect of CR1 in autoimmune patients will be detailed later.…”
Section: Cr1 (Cd35) and Cr2 (Cd21)mentioning
confidence: 98%